A review of the sustainable utilisation of red mud and fly ash for the production of geopolymer composites. (3rd October 2022) - Qaidi, Shaker M.A.; Tayeh, Bassam A.; Ahmed, Hemn Unis; Emad, Wael
Highlights: This study progresses a state-of-the-art review of red mud and fly ash for the production of geopolymer composites. The physical and chemical properties of RM-FAGPC is reviewed. The fresh and hardened properties of RM-FAGPC is discussed. The durability and microstructure properties of UHP-GPC is reviewed. Recommendations and observations are advanced for future research. Abstract: Cement manufacturing emits a lot of CO2, which adds to negative environmental effects, including global warming and climate change. These phenomena have reignited interest in using a range of industrial waste products to make geopolymer composites and alkali activated binders, with the goal of reducing the use of regular Portland cement in building construction. One of these toxic radioactive waste substances is red mud (RM), which is produced as a byproduct of Bayer's aluminium (Al) production process. The objective of this study is to undertake a state-of-the-art review of the literature on the usage of red mud and fly ash (FA) in the production of red mud-fly ash geopolymer composites (RM-FAGPC). The environmental and economic implications, physical and chemical characteristics, manufacturing, distribution, categorization, and prospective uses of red mud are all discussed. Furthermore, current advances in the use of red mud and FA for geopolymer synthesis in terms of physical, mechanical, durability, and microstructure characteristics are highlighted. Furthermore, this research aims to design a path toward a realistic valorisation that considers both actual and perceived problems, including leaching, radioactivity, and the life cycle evaluation of red mud geopolymer composites (RM-GPC). The potential usage of RM-FAGPC manufacturing highlights the need for more research into the combination and proportion of these two raw materials with other cement-based materials, which might lead to novel, cost-effective, and energy-saving construction processes and products. It is also suggested that investigative efforts be focused on ecological, economic, and life cycle analyses.